Pemikiran Ekonomi Ibnu Khaldun dan Al-Ghazali Serta Relevansinya Terhadap Perekonomian di Indonesia - Rahmat Hidayat; Fiantika Salwa Ibrahim; Mardawati (Yayasan Darussalam Patalassang, 2025)
The Islamic economic thought developed by great figures such as Ibn Khaldun and Al-Ghazali has contributed to understanding a just and prosperous economic system. This study examines Islamic economic thought according to Al-Ghazali and Ibn Khaldun and its relevance to the economy in Indonesia. This study uses a descriptive qualitative method with a literature study approach to describe the Prophet's economic policies systematically and analytically. The study results explain that Al-Ghazali emphasized the importance of ethics in economics, including aspects of morality in economic activities, fair distribution of wealth, and avoidance of usury and oppression practices. Meanwhile, Ibn Khaldun, with his